Predictors of Low Milk Volume among Mothers Who Delivered Preterm. (November 2014) - Murase, Masahiko; Nommsen-Rivers, Laurie; Morrow, Ardythe L.; Hatsuno, Misato; Mizuno, Katsumi; Taki, Motohiro; Miyazawa, Tokuo; Nakano, Yuya; Aizawa, Madoka; Itabashi, Kazuo
Background: Factors associated with successful provision of mother's own milk (MOM) for premature infants in a Japanese neonatal intensive care unit (NICU) context are not well known. Objective: We determined the independent risk factors for low milk volume at day 4 postpartum and formula feeding at the time of NICU discharge. Methods: We reviewed the medical records of mothers who delivered at < 32 weeks' gestation. We determined maternal, premature infant, and milk expression variables predictive of (1) day 4 postpartum milk volume being less than the cohort median and (2) formula feeding at the time of NICU discharge, reported as adjusted odds ratios (95% confidence interval). Results: Among 85 dyads, median (quartile range) milk volume on day 4 postpartum was 153 (34-255) mL. The rate of formula feeding at discharge was 42%. Mothers delivering by cesarean (vs vaginal) delivery had 4.3-fold (1.5-12.4) greater odds of day 4 milk volume < median ( P < .01). Pregnancy-induced hypertension, delayed milk expression initiation, and low pumping frequency were strongly associated with cesarean delivery. Subsequently, mothers with day 4 milk volume < median (vs ≥ median) had 7.1-fold (2.6-19.5) greater odds of formula feeding at discharge ( P < .01). Conclusion: Cesarean delivery is associated with lower milk volume on day 4 but may represent a composite of underlying risk factors for low milk volume in the early postpartum period. Further, low milk volume on day 4 is a strong correlate of lack of exclusive breast milk feeding at NICU discharge.